Structural changes of layered alkylsiloxanes during the reversible melting–solidification process. Issue 28 (30th June 2016) - Fujii, Kazuko; Hayashi, Shigenobu; Hashizume, Hideo; Shimomura, Shuichi; Jimura, Keiko; Fujita, Taketoshi; Iyi, Nobuo; Yamagishi, Akihiko; Sato, Hisako; Ando, Toshihiro
Abstract : Structural changes of layered alkylsiloxanes occurring during the reversible melting–solidification process were investigated by in situ XRD and NMR. Abstract : Through various in situ analyses, we have revealed the structural changes that occur during the reversible melting–solidification process of layered alkylsiloxanes (C n LSiloxanes) with carbon numbers ( n ) of 18 and 16. In situ high-resolution solid-state 13 C nuclear magnetic resonance (NMR) analysis at controlled temperatures indicates drastic conformational changes of the long alkyl chains during the melting–solidification process. A 13 C NMR signal at 33 ppm, which shows the highest intensity at room temperature (RT), is assigned to an inner methylene group with an all- trans conformation. As the temperature increases, the 33-ppm signal intensity decreases while the signal intensity at 30.5 ppm simultaneously increases. The 30.5 ppm signal is assigned to an inner methylene group with a trans – gauche conformation. Subsequently, upon cooling, the signal at 33 ppm recovers, even after C n LSiloxanes have melted. In situ X-ray diffraction measurements at controlled temperatures reveal that the ordered arrangement of the long alkyl chains becomes disordered with elevating temperatures and reordered upon cooling to RT. In situ high-resolution solid-state 29 Si NMR analysis shows that the melting–solidification process progresses without any structural change in siloxane sheets of the C n LSiloxanes. Thus, the in situ analyses show that disordering of the long alkyl chains causes the C n LSiloxanes to melt. Because the majority of long alkyl chains are packed again in the ordered arrangement with the all- trans conformation upon cooling, the C n LSiloxanes are reversibly solidified and the C n LSiloxane structure is recovered.